2016
DOI: 10.1097/gme.0000000000000635
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between sociodemographic, reproductive, and lifestyle factors and the severity of menopausal symptoms among Egyptian women in Alexandria

Abstract: Participant-related information such as working status, which was shown to increase the frequency of psychological symptoms in our ethnic group, should be noted by the physician, and a suitable approach should be adopted to achieve better therapy outcomes. Counseling about the importance of maintaining an ideal body weight and exercise should be emphasized to reduce menopausal symptoms. Appropriate advice and support in improving the overall state of the postmenopausal women is essential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Parity, although not found to be significant in this study, is another reproductive factor that has been identified to be associated with menopausal symptoms in women with natural menopause. In a study among Egyptian women, a significant positive association was observed between menopausal symptoms and the number of children 37 . In a large-scale population study, middle-aged Chinese women with parity ≥2 achieved higher total and subscale (somatic and urogenital) scorings of mKMI than women with nulliparity 12 .…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Parity, although not found to be significant in this study, is another reproductive factor that has been identified to be associated with menopausal symptoms in women with natural menopause. In a study among Egyptian women, a significant positive association was observed between menopausal symptoms and the number of children 37 . In a large-scale population study, middle-aged Chinese women with parity ≥2 achieved higher total and subscale (somatic and urogenital) scorings of mKMI than women with nulliparity 12 .…”
Section: Discussionmentioning
confidence: 92%
“…In a study among Egyptian women, a significant positive association was observed between menopausal symptoms and the number of children. 37 In a large-scale population study, middle-aged Chinese women with parity !2 achieved higher total and subscale (somatic and urogenital) scorings of mKMI than women with nulliparity. 12 However, these studies failed to include gravidity as covariates; thus, the significant effect of parity might be attributed to a close association between parity and gravidity.…”
Section: Menopausal Symptoms In Poi Womenmentioning
confidence: 99%
“…26,27 Eight socio-demographic and clinical variables (age, social support, menopausal stages, gravida para, menstrual status, chronic diseases, gynecological diseases, and major life events in the past year) were included in the matching procedure, following previous studies and our results. 7,[28][29][30][31][32] For the two groups, 1:4 tendency score matching was applied and the calipers value was set to 0.03. Standardized mean differences (SMD) were assessed to evaluate the balance of covariates before and after matching.…”
Section: Discussionmentioning
confidence: 99%
“…PSM is a statistical approach that estimates the effect of an action by balancing confounding factors that predict executing the action, which could minimize the effect of bias and ensure the highest possible level of evidence 26,27 . Eight socio-demographic and clinical variables (age, social support, menopausal stages, gravida para, menstrual status, chronic diseases, gynecological diseases, and major life events in the past year) were included in the matching procedure, following previous studies and our results 7,28-32 . For the two groups, 1:4 tendency score matching was applied and the calipers value was set to 0.03.…”
Section: Methodsmentioning
confidence: 99%